2021
DOI: 10.1080/16078454.2021.1972242
|View full text |Cite
|
Sign up to set email alerts
|

Variations and characteristics of the various clinical phenotypes in a cohort of Nigerian sickle cell patients

Abstract: Background: Sickle cell anaemia affects about 4 million people across the globe, making it an inherited disorder of public health importance. Red cell lysis consequent upon haemoglobin crystallization and repeated sickling leads to anaemia and a baseline strain on haemopoiesis. Vaso-occlusion and haemolysis underlies majority of the chronic complications of sickle cell. We evaluated the clinical and laboratory features observed across the various clinical phenotypes in adult sickle cell disease patients. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(50 reference statements)
2
1
0
Order By: Relevance
“…Although some of these studies included children >10 years, the study populations were primarily adults and also primarily SS/Sβ 0 genotypes, although the Nigerian study did not stratify by genotype. [1][2][3][5][6][7][8]26 A previous study at a single institution in Rio de Janeiro, Brazil, reported a similar prevalence to that found in the present research (23.4% in adults). 10 The present results provide an updated analysis of the prevalence of leg ulcers in a larger, more diverse representation of the Brazilian population with SCD.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although some of these studies included children >10 years, the study populations were primarily adults and also primarily SS/Sβ 0 genotypes, although the Nigerian study did not stratify by genotype. [1][2][3][5][6][7][8]26 A previous study at a single institution in Rio de Janeiro, Brazil, reported a similar prevalence to that found in the present research (23.4% in adults). 10 The present results provide an updated analysis of the prevalence of leg ulcers in a larger, more diverse representation of the Brazilian population with SCD.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of leg ulcers found in the present study (21%) is higher than what has been reported in the US (2.5%–18%), slightly lower than the prevalence reported in Jamaica (29%), and consistent with recent estimates in Nigeria (25%). Although some of these studies included children >10 years, the study populations were primarily adults and also primarily SS/Sβ 0 genotypes, although the Nigerian study did not stratify by genotype 1–3,5–8,26 . A previous study at a single institution in Rio de Janeiro, Brazil, reported a similar prevalence to that found in the present research (23.4% in adults) 10 .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation